Patient-reported rates of chronic pain and recurrence after groin hernia repair. Issue 1 (15th November 2017) - Lundström, K-J; Holmberg, H; Montgomery, A; Nordin, P
Abstract: Background: The effectiveness of different procedures in routine surgical practice for hernia repair with respect to chronic postoperative pain and reoperation rates is not clear. Methods: This was prospective cohort study based on a unique combination of patient-reported outcomes and national registry data. Virtually all patients with a groin hernia repair in Sweden between September 2012 and April 2015 were sent a questionnaire 1 year after surgery. Persistent pain, defined as at least 'pain present, cannot be ignored, and interferes with concentration on everyday activities' in the past week was the primary outcome. Reoperation for recurrence recorded in the register was the secondary outcome. Results: In total, 22 917 patients (response rate 75·5 per cent) who had an elective unilateral groin hernia repair were analysed. Persistent pain present 1 year after hernia repair was reported by 15·2 per cent of patients. The risk was least for endoscopic total extraperitoneal (TEP) repair (adjusted odds ratio (OR) 0·84, 95 per cent c.i. 0·74 to 0·96), compared with open anterior mesh repair. TEP repair had an increased risk of reoperation for recurrence (adjusted OR 2·14, 1·52 to 2·98), as did open preperitoneal mesh repair (adjusted OR 2·34, 1·42 to 3·71) at 2·5-year follow-up. No other methods of repair differed significantly from open anterior mesh repair. Conclusion: The risk of significant pain 1 year after groin hernia repair in routine surgical practice was 15·2 per cent. This figure was lower in patients who had surgery by an endoscopic technique, but at the price of a significantly higher risk of reoperation for recurrence. Abstract : Higher chronic pain rate than expected